UNDERWATER RESTAURANT BUILDING (TYPICAL STUDY: UNDER RESTAURANT BUILDING, SOUTHERN NORWAY) - septiawan, wawan; Purwantiasning, Ari Widyati (Talenta Publisher, 2021)
The underwater building is a building that has its uniqueness where this building in terms of its location is below the surface of the water, besides that this building has its uniqueness from the shape of the building, for example in a typical study of an underwater restaurant located in Southern Norway called restaurant Under This building was chosen because it is an underwater building and has its uniqueness in the building. Research on underwater buildings is carried out to find out what applications are used and what concepts are used in underwater buildings. For the data processing method using a comparative method where this research method is an analytical variable from the results of the combination between data from the theory of architectural elements and the principles of water. And produce a variable to analyze underwater buildings such as shape, space, color, and texture or material.